FRAMES AND REFRAMING IN MEDICINE FRAMES AND REFRAMING IN MEDICINE - Garrido Rodríguez, Natividad (Analysis. Journal of Philosophical Research, 2024)
In this work, the notion of “frame” is used as a strategy for analyzing medical space. I consider medicine to be an ideal example for understanding how frames operate and how changes in practice. The objective is to analyze narrative medicine as a particular case of reframing that allows the reconstruction of the classic frame in medicine, Evidence-Based Medicine (EBM). To do this, I will propose an analysis of both frames and I will study as a practical example the formal chart and the “parallel chart” proposed by narrative medicine. The “parallel chart” will be considered as a tool that complements the medical chart and that will allow new approaches and guides for interpretation and action in medical practice.